(untitled) (Archaeologia Adriatica, 2014)
Archaeology and its various branches (Prehistoric, Classical Antiquity, Mediaeval, Modern Era), as a part of the humanities, is a truly interdisciplinary science. Each of its dimensions is oriented towards the ways in which people have occupied spaces for thousands of years and the various forms of organisation this has taken. It can be said that archaeology operates in three dimensions. Apart from terrestrial archaeology, i.e. the usual field work, there is underwater archaeology (seas, lakes, watercourses) and also archaeology based on facts acquired from remote sensing, i.e. photos from space and the air. This paper focuses on this third dimension of archaeology, presenting examples of archaeological sites from the north of the Croatian archipelago, starting with Krk and continuing along the eastern Adriatic, including its hinterland, down to Pelješac (Ston).